Gene-Edited Meat: Disentangling Consumers' Attitudes and Potential Purchase Behavior - Martin-Collado, Daniel; Byrne, Tim J.; Crowley, Jonh J.; Kirk, Tom; Ripoll, Guillermo; Whitelaw, C. B. A. (Frontiers in Nutrition, 2022)
Novel gene-editing (GE) technologies provide promising opportunities to increase livestock productivity and to tackle several global livestock production sustainability and food security challenges. However, these technologies, as with previous genetic modification technologies in food production, are very likely to generate social controversy and opposition towards their use in the meat industry. Here, we explored public attitudes and consumption predisposition towards gene-edited meat products and their potential added benefits to livestock farming. Our results show that societal perception currently comes as a package, where the use of gene-editing technology acts as an extrinsic cue of meat products quality, and is used to make a range of inferences about all quality facets at once. Although consumers with anti-GE attitudinal positions generally were not sensitive to price discounts or added benefits, added benefits increased the consumption predisposition of most moderate and pro-GE consumers, where benefits related to animal welfare had larger effects than those relating to the environment or human health issues.